A sonographic assessment of previous caesarean section scar: is a reliable safeguard for trial of labour? - Dhama, Vandana; Gupta, Sonam; Chaudhary, Rachna; Singh, Shakun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Over the time the caesarean delivery rate has significantly increase worldwide from 18.2% in 2002 to 30.3% in 2012. In parous women, previous caesarean section has been found to be the most common indication for caesarean delivery in as high as 67% cases. Unsecure prediction of the integrity of the scarred LUS during labor appears to be one of the reasons for high repeat caesarean rates. The purpose of this study was to assess the usefulness of sonographic measurement of the lower uterine segment scar before labour for deciding whether it is a reliable safeguard for trial of labour or not in a woman having previous one caesarean delivery. Methods: This study was a prospective observational study, carried out on 108 pregnant women having previous one CS, gestational age >37, singleton pregnancy, cephalic presentation. Trans-abdominal USG was done to measure scar thickness. Trial of labour was given to each patient irrespective of scar thickness. Pregnancy outcome were noted in terms of successful VBAC or emergency LSCS and compared with scar thickness. Correlation between sonographic and intra-operative finding of scar were noted. Results: Result shows strong correlation between scar thickness and successful trial of labour. Scar thickness increases chances of successful vaginal deliveries. Conclusions: Sonographic assessment of previous scar has a practical application to predict the thickness and thinness of previous scar and can be taken as a reliable safeguard for trial of labour after previous cesarean but cut off value above which vaginal delivery could be considered safe is yet to be identified.